Placental Pathology Findings and the Risk of Intraventricular and Cerebellar Hemorrhage in Preterm Neonates - Parodi, Alessandro; De Angelis, Laura Costanza; Re, Martina; Raffa, Sarah; Malova, Mariya; Rossi, Andrea; Severino, Mariasavina; Tortora, Domenico; Morana, Giovanni; Calevo, Maria Grazia; Brisigotti, Maria Pia; Buffelli, Francesca; et al. (Frontiers in Neurology, 2020)
Placental pathology as a predisposing factor to intraventricular hemorrhage remains a matter of debate, and its contribution to cerebellar hemorrhage development is still largely unexplored. Our study aimed to assess placental and perinatal risk factors for intraventricular and cerebellar hemorrhages in preterm infants. This retrospective cohort study included very low-birth weight infants born at the Gaslini Children’s Hospital between January 2012 and October 2016 who underwent brain magnetic resonance with susceptibility-weighted imaging at term-equivalent age and whose placenta was analyzed according to the Amsterdam Placental Workshop Group Consensus Statement. Of the 286 neonates included, 68 (23.8%) had intraventricular hemorrhage (all grades) and 48 (16.8%) had a cerebellar hemorrhage (all grades). After correction for gestational age, chorioamnionitis involving the maternal side of the placenta was found to be an independent risk factor for developing intraventricular hemorrhage, whereas there was no association between maternal and fetal inflammatory response and cerebellar hemorrhage. Among perinatal factors, we found that intraventricular hemorrhage was significantly associated with cerebellar hemorrhage (odds ratio [OR], 8.14), mechanical ventilation within the first 72 h (OR, 2.67), and patent ductus arteriosus requiring treatment (OR, 2.6), whereas caesarean section emerged as a protective factor (OR, 0.26). Inotropic support within 72 h after birth (OR, 5.24) and intraventricular hemorrhage (OR, 6.38) were independent risk factors for cerebellar hemorrhage, whereas higher gestational age was a protective factor (OR, 0.76). Assessing placental pathology may help in understanding mechanisms leading to intraventricular hemorrhage, although its possible role in predicting cerebellar bleeding needs further evaluation.